Analysis of Ground Water Quality Status in Tambakboyo Hamlet, Tikung District, Lamongan Regency Using Storet Method - Rodu Dhuha Afrianisa; Pratama Sandi Alala; Taty Alfiah; Nazilatun Niswa; Erlinda Ningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
Leachate from the Tambakrigadung Final Disposal Site has potential to contaminate ground water of residents in Tambakboyo Hamlet, Tambakrigadung Village, Tikung District, Lamongan Regency. Tambakboyo Hamlet is a residential area close to the Tambakrigadung TPA. This study was aimed at determining the effects of the distance between the well and the Tambakrigadung landfill on the water quality of the Tambakrigadung residents' wells. The sampling employed a purposive technique by taking water samples from dug wells belonging to residents. Sampling occurred at 7 points within 3 repetitions, taking into account the distance of the well from the landfill. To determine the level of contamination in the wells being studied, the researcher applied the STORET method. Water quality status based on storet method at points A, F and G has score -19, -11. -15, and poiytnt B,C,D,E has score -7,-5,-7,-5. The results of this study indicated that 3 wells belonged to a moderately polluted, and 4 well was categorized as having a lightly polluted.